LA REFLEXIÓN SOBRE EL LENGUAJE A PARTIR DE OBRAS LITERARIAS (De la Crítica, 2023)
Language is so enveloping that it usually goes unnoticed by the common subject. Yet it has fascinated the restless minds of philosophers, linguists, and writers. This work aims to analyze the theme of language from the treatment given to it in selected texts (The writing of the god, The Aleph; The alarms of doctor Américo Castro; The analytical language of John Wilkins; A reader; To the German language) of the three genera cultivated by Jorge Luis Borges. This refers to a type of Descriptive research, with a Documentary design. It is developed based theoretically on the Critique of Language. Through the analysis carried out, it is concluded that language appears as a theme in the texts studied, and that from these it is possible to propose reflection, especially on the characteristics or aspects of Language highlighted by Borges, such as: the limits of language, its self-refentiality, the need to understand the code to capture a message, linearity of the sign, anti-dogmatism against linguistic purism, concern for a universal and less arbitrary language, polyglot and literary interest in the beauty of language.